Pollution risk from Pb towards vegetation growing in and around shooting ranges – a review. Issue 1 (1st January 2021) - Dinake, Pogisego; Mokgosi, Serwalo Mercy; Kelebemang, Rosemary; Kereeditse, Tsotlhe Trinity; Motswetla, Obakeng
ABSTRACT: Commissioned and de-commissioned shooting ranges continue to pose an environmental and human health risk due to the accumulation of toxic Pb emanating from spent munitions. The phytotoxic effects of Pb accumulation in plants include inhibition of root growth and lowering of plant metabolism. The uptake of Pb by plants is directly affected by factors such as plant species and physicochemical properties of the soil. However, scientists and researchers have leveraged on the ability of some plant species to accumulate and tolerate Pb toxicity and applied them in the control and management of Pb pollution of shooting range soils. This technique is called phytoremediation. The objectives of this review are: (i) to assess the prevalence of toxic Pb metal in plant species growing in and nearby shooting ranges, (ii) to establish the soil-plant mechanistic pathway for Pb (iii) discuss the effectiveness of phytoremediation technology towards shooting range soil amendment.